A cost effective and consummate fabrication teaching set up for microelectronic engineering undergraduate - Uda, Hashim, Prof. Dr. (Malaysian Invention & Design Society (MINDS), 2010)
Prof. Dr. Uda Hashim and his team won gold for A Cost Effective and Consummate Fabrication Teaching Set Up For Microelectronic Engineering Underaduate. ITEX 2005, 19th - 21st May 2005 was held at Putra World Trade Centre (PWTC), Kuala Lumpur.